Adaptation of Perceived Parental Autonomy Support (P-PASS) on College Students 18-24 Years Old - Alifah, Atri Fathia; Lubis, Fitriani Yustikasari (Psikostudia : Jurnal Psikologi, 2024)
Emerging adulthood who having a parental support for autonomy and reduced control exerted will show a high self-esteem. In addition, this is also related to his success in academic. Because emerging adulthood is related to college student age. So it is important to be able to measure the parental autonomy support and controlling parents obtained by students in Indonesia. This measurement tool for perceived parental autonomy was developed by Mageau in 2015 and has never been adapted in Indonesia. This study aims to evaluate the validity and reliability of the perceived parental autonomy support measuring instrument in Indonesian. Content validity for this measure uses CVI. Then use CTT to analyze reliability and discrimination items. Participants in this study were 272 students who were collected using accidental sampling technique. The results of the adapted measuring instrument are relevant for measuring the construct, by liberating the three items on the controlling parent dimension, the CVI valuesfor each dimension are 1 and .98, while the reliable values are .93 and .87. In the CFA results, the fit model can be accepted on every dimension.Emerging adulthood yang mendapatkan dukungan otonomi orang tua dan pengurangan kontrol yang diberikan akan menunjukkan self-esteem yang tinggi dan juga berkaitan dengan keberhasilannya di akademik. Dikarenakan usia emerging adulthood berada pada 18-24 tahun yang sebagian besar berprofesi sebagai mahamahasiswa. Maka dari itu, penting untuk dapat mengukur parental autonomy support dan controlling parent yang didapatkan oleh mahasiswa. Alat ukur perceived parental autonomy support ini dikembangkan oleh Mageau tahun 2015 dan belum pernah diadaptasi di Indonesia. Penelitian ini bertujuan untuk mengevaluasi validitas dan reliabilitas alat ukur perceived parental autonomy support dalam bahasa Indonesia. Validitas konten untuk alat ukur ini menggunakan CVI. Kemudian menggunakan CTT untuk menganalisis reliabilitas dan diskriminasi aitem. Partisipan pada penelitian ini yaitu mahamahasiswa sebanyak 272 yang dikumpulkan menggunakan teknik sampling insidental. Hasil alat ukur yang diadaptasi relevan untuk mengukur konstruk, dengan membebaskan tiga item pada dimensi controlling parent didapatkan nilai CVI untuk setiap dimensi yaitu 1 dan .98, sedangkan untuk nilai reliabel yaitu .93 dan .87. Pada hasil CFA, model fit dapat diterima pada setiap dimensi.